A37 Buccal respiratory chain complexes I and IV quantities in huntington's disease patients. (September 2018) - Dusek, Pavel; Rodinova, Marie; Liskova, Irena; Klempir, Jiri; Zeman, Jiri; Roth, Jan; Hansikova, Hana
Abstract : Alterations in mitochondrial parameteres are an important hallmark of Huntington's disease (HD). Given the ubiquitous expression of mutant huntingtin raises the prospect that mitochondrial disturbancies can be detected and monitored also in buccal epithelial cells. In a group of 34 patients with Huntington's disease and a group of 22 age-related healthy volunteers, respiratory complex I and IV protein quantities in buccal epithelial cells were measured using dipstick immunocapture assay. The protein quantity of respiratory complex I is correlated with age (r=0.427, p=0.026, FWE-p=0.156) in the patient group, but not in the group of healthy subjects. Our non-invasive approach allows to obtain valuable materials for studies on mitochondrial biochemical parameters in patients with neurodegenerative diseases and could be be useful in epidemiological studies.